The Influence of the Ability to Read the Quran on Learning Outcomes in High School - Raniza, Yuratika; Nazaruddin, Nazaruddin; Andahurifky, Andahurifky; Nurhaliza, Pioni; K, Munawir; Dahliana, Dina (Suluah Pasaman, 2023)
The personality competence of teachers plays a crucial role in shaping students' learning experiences and motivation. This study aims to analyse the personality competence of Islamic Education teachers at Senior High Schools and its correlation with student learning motivation. This research employs a quantitative approach to analyse the influence of the ability to read and write the Quran on learning outcomes in Islamic education subjects for Class XI students at High Schools. Data were collected from 44 randomly selected students using a Likert scale to measure attitudes, opinions, and perceptions regarding learning methods. The data were analysed using simple linear regression and correlation coefficients. The results of the study show that the ability to read and write the Quran has a significant positive influence on learning outcomes. The hypothesis test results indicate that the significance value (sig) is 0.783, which is greater than 0.05 (0.783 > 0.05), leading to the acceptance of Ho and rejection of Ha. The correlation test results further demonstrate a positive and significant relationship between students' ability to read and write the Quran and their learning outcomes in Islamic education. This suggests that enhancing students' Quranic reading and writing skills can positively impact their academic performance in Islamic education subjects.